Exploring Lexemic Idiomatic Expressions in Robert Their’s Wattpad Novel “Storm and Silence” - Surbakti, Tiara Sari; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (PROJECT (Professional Journal of English Education), 2025)
This research explores the use of lexemic idiomatic expressions in Robert Thier's Wattpad novel "Storm and Silence" and their literal meanings. The research employs a descriptive qualitative method to identify and categorize idiomatic expressions within the text. This research uses semantics by using Makkai's theory. The data presented taken from Robert Thier's Wattpad novel Storm and Silence; 106 data were found. The result of this research is that tournure idioms are the most prevalent 48 (45%), followed by phrasal verb idioms 19 (18%) and phrasal compound idioms 14 (13%). Pseudo-idioms 11 (10%). Interestingly, the irreversible binomial idiom contains 8 (8%), whereas the incorporation verb is 6 (6%). The result highlight the significance of idiomatic expressions in enhancing character development and thematic depth while presenting challenges for readers unfamiliar with idiomatic expressions. This research contributes to understanding idiomatic expressions in contemporary literature, particularly on digital platforms like Wattpad. It raises awareness among readers regarding the cultural nuances embedded in idiomatic language. The research suggests that further research could expand the dataset and duration to enrich the analysis of idiomatic expressions across various literary genres.